Study of karst manifestations in Solotvyno based on aerial photography from a UAV - Hlotov Volodymyr; Shylo Yevhenii; Yatskivskyi Yaroslav; Kablak Nataliya; Nychvyd Mariya (Reports on Geodesy and Geoinformatics, 2023)
This article is devoted to the study of surface karst manifestations on the territory of inactive salt mines of Solotvyno, Transcarpathian region, Ukraine. The historical development of the salt mine from the moment of the creation of the first mine (the end of the 18th century) to the present is considered. Based on the results of previously published studies, monitoring of karst manifestations from 2010 to 2020 was implemented. The last stage of monitoring in 2021 was the aerial survey of the territory obtained by the Arrow UAV using the Sony QX1 camera. Pix4Dmapper software was used for image processing. The aim of the work is to estimate the scale of destructive geological processes by the method of photogrammetry. During the execution of the work, the methods of processing materials of aerial photography, analysis of developments in the direction of photogrammetry were applied. As a result of the study, the volume-planar characteristics of karst formations on the territory of Solotvyno were calculated using the photogrammetry method. This scientific work is relevant for assessing the scale of the development of degenerative geological processes on the territory of Ukraine, in particular within the Transcarpathian region. The practical significance of the obtained results lies in their application in order to ensure environmental monitoring. The results of the study can be used to predict the impact on economic and infrastructure objects, followed by the development of a plan of specific actions for prevention, localization and work with the consequences of man-made processes in the adjacent territory.